Anticorpos vacinais virais em crianças portadoras de Leucemia Linfóide Aguda após quimioterapia - Viana, Simone Santana (2009)
The role of vaccination in children, who received chemotherapy for malignancies, including acute lymphoblastic leukemia (ALL), remains controversial. Both the disease and treatment affect the immune system. Changes may occur by neutropenia, leading to immediate risk of bacterial and fungal infections, loss protective levels of antibody by previous immunizations, as well as the questionable efficacy of revaccination. Therefore, different approaches are applied in several countries and the best vaccination schedule is not well defined yet. Moreover, the existing recommendations, mainly built on low levels of evidence, are not always followed by oncologists in clinical practice and there are still few references to literature on the subject. The paucity of data from controlled trials on both residual immunity against vaccine antigens at the end of treatment of children with ALL and the ability of the patients to respond to vaccine boosters does not allow the development of guidelines, and then further evaluation are required. We conducted a study using open controlled clinical trial to assess the levels of protection against viral vaccine antigens in children treated for leukemia after completion of chemotherapy, and implementation of a booster dose vaccine. Serum antibody levels were evaluated for hepatitis B, measles, rubella and mumps in 33 patients and compared with a control group. Statistical analysis was performed using the Chi-square and Fisher exact tests for categorical variables and Mann-Whitney test for continuous variables. As a result, there was a high proportion of individuals not immune to measles (75.9%), to rubella (51.7%) and hepatitis B (59.3%) at the end of chemotherapy for ALL. After administration of one booster dose of vaccine, had a recovery for all antigens tested was statistically significant for measles (p = 0, 0422) and hepatitis B (p = 0.0357). It is recommended, therefore, administration of one dose of the MMR and evaluate vaccine antibody titers for individual interventions.